Diversidade, variação sazonal e importância econômica dos afídeos (Homóptera: Aphidoidea) na Estação Ecológica de Jataí (Luiz Antônio - SP) e nas áreas agrícolas e de silvicultura do entorno - Fabrício, Tárcio Minto (2003)
The majority of the studies related to aphids in Brazil has been exclusively focused on species with agricultural importance, and just a part of them concerning about the species associated to natural areas. In this way it was objectified in the present work to estimate the diversity of aphids species in the Ecological Station of Jataí (Luiz Antonio-SP) and in the agricultural and artificial forested areas of its surroundings, and to verify its composition, organization and seasonality. The aphids had been collected from January to December of 2001, and they were captured with Moericke traps, at six points located in different categories of land use in the study area: plantation of Pinus ellioti, Cerradão, Cerrado, plantation of Eucaliptus spp., culture of Citrus sp. and culture of sugar cane. It was captured a total of 2593 individuals of 17 species, Aphis craccivora Koch, 1854; Aphis fabae/solanella; Aphis gossypii Glover, 1877; Aphis spiraecola Patch 1914; Toxoptera aurantii (Boyer de Fonscolombe, 1841); Toxoptera citricidus (Kirkaldy, 1907); Rhopalosiphum maidis (Fitch, 1856); Rhopalosiphum nymphaeae (Linnaeus, 1761); Acyrthosiphon bidenticola Smith, 1960; Myzus persicae (Sulzer, 1776); Pentalonia nigronervosa Coquerel, 1859; Uroleucon ambrosiae (Thomas, 1878); Lizerius ocotea Blanchard, 1923; Cinara fresai Blanchard, 1939; Cinara maritimae (Dufour, 1833); Eulachnus rileyi (Williams, 1911); Tetraneura nigriabdominalis (Sasaki, 1899). The sampled natural areas, Cerrado and Cerradão, were responsible for the highest values of diversity, H = 2,24 and HB = 2,14 and H = 2,05 and HB = 1,82 respectively. The plantation of Eucaliptus and the culture of Citrus had presented intermediate values, respectively H = 1,85 and HB = 1.77; H = 1,17 and HB = 1.09. The lowest values of diversity were obtained for the culture of sugar cane and the plantation of Pinus, with: H = 0,669 and HB = 0.63; H = 0,621 and HB = 0.605, respectively. The plantation of Pinus sp. , Eucaliptus spp. and Citrus sp. exhibited a higher similarity in relation to the occurrence of the species of aphids. The association between the species in the spatial and temporal scale showed different patterns of grouping. The dry season of the year was responsible for the highest number of captured individuals, and it was preferred for 8 of the 17 species. The climatic factors with the highest influence in the variation of the populations were the temperature, the rainfall and the photoperiod. The climatic variations had possibly been the key-factor in the regulation of the populations in the areas with lower antropic disturbs. The polyphagous aphids had been the majority, however, the monophagous species showed a higher number of individuals. In 17 captured species, 11 were classified as species with agricultural importance in the study area. The species with higher potential of damage were U. ambrosiae, T. citricidus and E. rileyi. The natural areas had presented a low number of species with economic importance.